An Improved Technique for Chromosomal Analysis of Human ES and iPS Cells - Moralli, D; Yusuf, M; Mandegar, M; Khoja, S; Monaco, Z; Volpi, E (2011)
Prolonged in vitro culture of human embryonic stem (hES) cells can result in chromosomal abnormalities believed to confer a selective advantage. This potential occurrence has crucial implications for the appropriate use of hES cells for research and therapeutic purposes. In view of this, time-point karyotypic evaluation to assess genetic stability is recommended as a necessary control test to be carried out during extensive 'passaging'. Standard techniques currently used for the cytogenetic assessment of ES cells include G-banding and/or Fluorescence in situ Hybridization (FISH)-based protocols for karyotype analysis, including M-FISH and SKY. Critical for both banding and FISH techniques are the number and quality of metaphase spreads available for analysis at the microscope. Protocols for chromosome preparation from hES and human induced pluripotent stem (hiPS) cells published so far appear to differ considerably from one laboratory to another. Here we present an optimized technique, in which both the number and the quality of chromosome metaphase spreads were substantially improved when compared to current standard techniques for chromosome preparations. We believe our protocol represents a significant advancement in this line of work, and has the required attributes of simplicity and consistency to be widely accepted as a reference method for high quality, fast chromosomal analysis of human ES and iPS cells. © 2011 The Author(s).